Snapseed As A Digital Bridge: Tam-Based Product Photo Editing Training On Traditional Culinary MSMEs Tam Approach - Guntoro Barovih; Fahmi Ajizmanto (Inaba of Community Services Journal, 2026)
Inadequate product photography represents a persistent barrier to effective digital marketing among micro-scale culinary enterprises in Indonesia. This community service study aimed to enhance the digital marketing capacity of MSME Dapoer KuKia through structured product photo editing training using the Snapseed mobile application, while evaluating technology acceptance using the Technology Acceptance Model (TAM). The program was implemented over eight weeks through a Participatory Action Research (PAR) approach, comprising four structured training sessions and guided independent practice. A 14-item TAM questionnaire with established content validity was administered at pre- and post-intervention time points, and changes were assessed using the Wilcoxon Signed-Rank Test. Results confirmed significant improvements across all four TAM constructs (W = 0, N = 14, p < 0.05). Perceived Ease of Use recorded the highest improvement, increasing from a mean of 2.00 to 4.50 (+125.0%), followed by Perceived Usefulness from 2.25 to 4.25 (+88.9%), and both Attitude toward Using and Behavioral Intention to Use from 3.00 to 4.67 (+55.6%). These findings demonstrate that contextual, hands-on mobile technology training effectively dismantles perceived complexity barriers and enhances technology acceptance among micro-scale culinary MSME practitioners.